Phylogenomic analyses and chromosome ploidy identification reveal multiple cryptic species in Allium sikkimense complex (Amaryllidaceae) - Huang, De-Qing; Ma, Xiang-Guang; Sun, Hang (Frontiers in Plant Science, 2024)
Polyploidization is a process that typically leads to instantaneous reproductive isolation, and has therefore been considered as one of the major evolutionary forces in the species-rich Hengduan Mountains (HM), yet this topic remains poorly studied in the region. Allium sikkimense and its relatives (about 8 species) compose a natural diploid-polyploid complex with the highest diversity in the HM and adjacent areas. A combination of nuclear ribosomal DNA (nrDNA), plastome, transcriptome, and ploidy identification through chromosome counting and flow cytometry is employed to reconstruct the phylogenetic relationships in this complex, and to investigate the frequency and the evolutionary significance of polyploidy in the complex. The plastome failed to resolve the phylogenetic relationships of the different species in the A. sikkimense complex, and the phylogenetic tree based on nrDNA also has limited resolution. However, our study reveals a well-resolved phylogenetic framework for species in the A. sikkimense complex using more than 1000 orthologous genes from the transcriptome data. Previously recognized morphospecies A. sikkimense are non-monophyletic and comprise at least two independently evolved lineages (i.e. cryptic species), each forming a clade with different diploid species in this complex. The embedded pattern of octoploid A. jichouense and tetraploid A. sp. nov within different polyploid samples of A. sikkimense supports a possible scenario of budding speciation (via niche divergence). Furthermore, our results reveal that co-occurring species in the A. sikkimense complex usually have different ploidy levels, suggesting that polyploidy is an important process for reproductive isolation of sympatric Allium species. Phylogenetic network analyses suggested that the phylogenetic relationships of the A. sikkimense complex, allowing for reticulation events, always fit the dataset better than a simple bifurcating tree. Additionally, the included or exserted filaments, which have long been used to delimit species, are highly unreliable taxonomically due to their extensive parallel and convergent evolution.